Implementing a Just Culture: Perceptions of Nurse Managers of Required Knowledge, Skills and Attitudes - Michelle Freeman, Linda A. Morrow, Margo Cameron and Karen McCullough (Nursing Leadership, 2016)
Background: Healthcare organizations have been challenged to create a just culture as part of their culture of safety. Purpose: To explore perceptions of nurse managers in developing personal competencies in order to enable them to effectively implement a just culture in their units. Method: Qualitative content analysis of semi-structured interviews with nine nurse managers identified themes. Data were independently analyzed by three members of the research team. Findings: Analysis of interview transcripts identified the following four themes: need for education of managers and employees, need for a variety of new skills for nurse managers, need to change attitudes from the long-standing punitive culture and fault of individual and challenges in implementation because of time constraints. Conclusion: Implementing a just culture is complex. Education of nurse managers is crucial. A series of educational strategies is recommended. Findings support the need for new competencies to enable nurse managers to effectively implement a just culture in their units.
Keywords: nursing leadership, just culture, workplace health, workplace ethics